Applying embedded program evaluation for care delivery transformation: An analysis of a home‐based urgent care program. Issue 5 (26th August 2022) - Carlson, Lucas C.; Pu, Charles T.; Mark, Eden; Gao, Ya; Nussbaum, Lisa; Vogeli, Christine
Abstract: Background: In 2014, Mass General Brigham, formerly Partners HealthCare, launched a novel urgent home‐based medical care program to provide rapid medical evaluation and treatment to homebound patients and older adults with frailty or limited mobility named the partners mobile observation unit (PMOU) program. Methods: We conducted a pragmatic, embedded evaluation assessing the impact of PMOU on postreferral utilization and total medical expenditure (TME). We used propensity weighting and logistic regression to estimate the 30‐day adjusted odds ratios (ORs) of emergency department (ED) utilization and inpatient medical hospitalization for patients enrolled in PMOU (891 episodes of care) relative to those who were referred but not enrolled in the program (57 episodes of care) during the period of April 2017 to June 2018. We additionally conducted a difference‐in‐differences analysis assessing program impact on TME, comparing claims data 30 days pre/post referral. Results: Despite positive trends, there were no statistically significant differences between the two groups with regard to postreferral ED visits or hospitalizations, with an OR of 0.83 ( p  = 0.56) and OR of 0.64 ( p  = 0.21), respectively. There was no statistically significant difference in pre/post referral TME for intervention relative to control episodes ( p  = 0.64). In post hoc analysis of control episodes, 75% received care elsewhere within 14 days of referral. Conclusion: Although the results suggested positive trends, this analysis of this relatively mature program was unable to identify statistically significant reductions in ED visits, hospitalizations, or TME associated with the PMOU program. Future efforts to build home‐based urgent care programs or related programs targeting older adults with frailty or limited mobility should aim to improve patient targeting and identify opportunities to improve program operations and generate meaningful reductions in healthcare utilization and spending.